2005
DOI: 10.1177/0193945905275936
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Phenomena of Women’s Postabortion Experiences

Abstract: A phenomenological approach was used to examine the responses of women to elective abortion. Sixteen women who terminated a pregnancy for nonmedical reasons at least 15 years previously participated. These women were caught up in the moment, they made a decision, had an abortion, and life continued-for some as before, for others, forever altered. Women encountered a sense of disruption. The abortion and reflections about the experience existed as an unspoken story, confided to few. Thoughts of this past experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Moreover, participants provided information regarding whether they (or their wives) had experience with abortion before the child's death (spontaneous, elective, or forced abortion), because previous abortion could result in postabortion grief that might have a long-term effect in terms of their relationships, sense making, and sense of self (Trybulski, 2005). Other significant bereavements (e.g., close friends, important relatives, parents, brothers or sisters, etc.)…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Moreover, participants provided information regarding whether they (or their wives) had experience with abortion before the child's death (spontaneous, elective, or forced abortion), because previous abortion could result in postabortion grief that might have a long-term effect in terms of their relationships, sense making, and sense of self (Trybulski, 2005). Other significant bereavements (e.g., close friends, important relatives, parents, brothers or sisters, etc.)…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Although research that discusses the effects of abortion for women of all ages is relevant and applicable, research specific to the adolescent abortion experience would be more meaningful and more likely to evoke a change in behavior for this age group. Adolescents might benefit from research findings, similar to those found in Trybulski's (2005) study, regarding how abortion affects peer relationships, changes the still maturing body, and influences relationships with the opposite sex.…”
mentioning
confidence: 54%
“…I applaud Trybulski's (2005) article, entitled "The Long-Term Phenomena of Women's Postabortion Experiences," for focusing on more than just the short-term effects of abortion. A person can change a great deal in 15 plus years, and this time can help one heal, grieve, learn from the process, develop a line of reasoning to rationalize the "in the moment" decision, or bring closure to the event.…”
mentioning
confidence: 99%
“…33 Increased secrecy, the study claims, leads to the development of thought suppression, an increase in intrusive thoughts, and that decreased emotional openness may be a factor in postabortion resolution. Similarly, a cross-sectional study of 797 women who underwent surgical abortion in the USA found that the desire for anonymity when using abortion services led many eligible women to decline claiming against their medical insurers for their treatment.…”
Section: Concealment Of Abortionmentioning
confidence: 99%
“…a pregnancy that was initially wanted) and this is associated with post-abortion psychological implications. 33 According to Avalos, the passage of time allows women to address issues they were not able to process or articulate at the time of the abortion. Avalos' empirical study of in-depth interviews with 20 women who had experienced abortion postulates that this might be because personal growth and changing circumstances prompt women to re-evaluate the original experience, and that retrospective interpretations of the abortion experience are subject to change over time.…”
Section: Making the Decisionmentioning
confidence: 99%